2019
DOI: 10.1074/jbc.ra118.005554
|View full text |Cite
|
Sign up to set email alerts
|

The reactive form of a C–S bond–cleaving, CO2-fixing flavoenzyme

Abstract: Edited by Ruma Banerjee NADPH:2-ketopropyl-coenzyme M oxidoreductase/carboxylase (2-KPCC) is a bacterial disulfide oxidoreductase (DSOR) that, uniquely in this family, catalyzes CO 2 fixation. 2-KPCC differs from other DSORs by having a phenylalanine that replaces a conserved histidine, which in typical DSORs is essential for stabilizing the reduced, reactive form of the active site. Here, using site-directed mutagenesis and stopped-flow kinetics, we examined the reactive form of 2-KPCC and its single turnover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…Moreover, acetone formation by F501H was comparable in rate to the carboxylation reaction catalyzed by WT 2-KPCC and leading to acetoacetate. These results are consistent with kinetic analyses that showed that Cys–disulfide reduction by NADPH is rate limiting in 2-KPCC ( 3 ) and insensitive to the F501H substitution.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Moreover, acetone formation by F501H was comparable in rate to the carboxylation reaction catalyzed by WT 2-KPCC and leading to acetoacetate. These results are consistent with kinetic analyses that showed that Cys–disulfide reduction by NADPH is rate limiting in 2-KPCC ( 3 ) and insensitive to the F501H substitution.…”
Section: Resultssupporting
confidence: 91%
“…Our recent work has suggested that the catalytic dyad differences observed in 2-KPCC go beyond that of simply limiting protonation in the promotion of carboxylation. We have shown that 2-KPCC operates through a different key reactive intermediate than GR (5) in which the reduced state of the redox active dithiol exists with a bridged single proton instead of the FAD-CysCT species observed in GR (Scheme 1B, 1C). We can see in our structure of the F501H variant and the structure of GR that the interactions of His with the exchange thiol (CysINT (C82)) would promote the stabilization of the GR-type reduced reactive intermediate relative to the 2-KPCC intermediate through stabilizing the more formal thiolate.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations